Clinical presentation and management of dyskinetic cerebral palsy. Issue 9 (September 2017) - Monbaliu, Elegast; Himmelmann, Kate; Lin, Jean-Pierre; Ortibus, Els; Bonouvrié, Laura; Feys, Hilde; Vermeulen, R Jeroen; Dan, Bernard
Summary: Cerebral palsy is the most frequent cause of severe physical disability in childhood. Dyskinetic cerebral palsy (DCP) is the second most common type of cerebral palsy after spastic forms. DCP is typically caused by non-progressive lesions to the basal ganglia or thalamus, or both, and is characterised by abnormal postures or movements associated with impaired tone regulation or movement coordination. In DCP, two major movement disorders, dystonia and choreoathetosis, are present together most of the time. Dystonia is often more pronounced and severe than choreoathetosis, with a major effect on daily activity, quality of life, and societal participation. The pathophysiology of both movement disorders is largely unknown. Some emerging hypotheses are an imbalance between indirect and direct basal ganglia pathways, disturbed sensory processing, and impaired plasticity in the basal ganglia. Rehabilitation strategies are typically multidisciplinary. Use of oral drugs to provide symptomatic relief of the movement disorders is limited by adverse effects and the scarcity of evidence that the drugs are effective. Neuromodulation interventions, such as intrathecal baclofen and deep brain stimulation, are promising options.